2015
DOI: 10.1039/c4an02127d
|View full text |Cite
|
Sign up to set email alerts
|

Label-free imaging and identification of typical cells of acute myeloid leukaemia and myelodysplastic syndrome by Raman microspectroscopy

Abstract: In clinical practice, the diagnosis and classification of acute myeloid leukaemia (AML) and myelodysplastic syndrome (MDS) start from the manual examination of stained smears of bone marrow (BM) and peripheral blood (PB) by using an optical microscope. This step is subjective and scarcely reproducible. Therefore, the development of subjective and potentially automatable methods for the recognition of typical AML/MDS cells is necessary. Here we have used Raman spectroscopy for distinguishing myeloblasts, promye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 32 publications
6
60
0
2
Order By: Relevance
“…was found in leukemia cells as compared to BMC, suggesting a decrease in the percentage of phenylalanine relative to the total SERS-active constituents in cells. This is consistent with R. Vanna's report on lower Raman signal of phenylalanine in myeloid leukemia cells [4]. In addition, compared with normal cells (BMC), the SERS peaks at 670, 802 and 896 cm −1 , related to thymine/guanine, uracil and ribose-phosphate respectively, exhibited lower signal in HL60 cells and K562 cells, suggesting that there was abnormal proliferation of DNA or RNA in leukemia cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…was found in leukemia cells as compared to BMC, suggesting a decrease in the percentage of phenylalanine relative to the total SERS-active constituents in cells. This is consistent with R. Vanna's report on lower Raman signal of phenylalanine in myeloid leukemia cells [4]. In addition, compared with normal cells (BMC), the SERS peaks at 670, 802 and 896 cm −1 , related to thymine/guanine, uracil and ribose-phosphate respectively, exhibited lower signal in HL60 cells and K562 cells, suggesting that there was abnormal proliferation of DNA or RNA in leukemia cells.…”
Section: Discussionsupporting
confidence: 80%
“…Since more than a decade ago, Raman microscopy has been a promising analytical tool for researchers working in the field of biomedical research, primarily because it is capable of detecting molecular vibrations that provide molecular information, including its structure and its environment [2]. Raman spectroscopy combined with statistical methods has been widely applied in disease diagnostics, including leukemia, oesophagus cancer, breast cancer, colorectal cancer, bladder cancer, lung cancer, and skin cancer [3][4][5]. However, the conventional Raman spectroscopy technique has many disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the increases of peaks at 1340 cm -1 (α-helices), after Raman analysis, denoted a greater sensitivity of collagen to molecular orientation, at dentin, in order to enhance further crystallization ). Furthermore, the ratio amide I/amide III raised and Raman CH2 signal diminished at dentin when samples were treated with Ca-NPs after 21 d of SBFS storage, indicating better organization of collagen with improved conformation of the polypeptide chains and lower immature stage of the dentin substrate, respectively (Vanna et al, 2015;Wang et al, 2009;Xu and Wang, 2011) (Table 4). Nevertheless, FWHMC of the carbonate band decreased after 21 d, though MMRC increased (Tables 3a, 3b).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of amide I peak indicates damage or removal of collagen fibrils (Xu and Wang, 2012). 1450 cm -1 (CH2 deformation bands) is generally assigned to proteins, lipids and carbohydrates; it is in accordance with the immature stage (Vanna et al, 2015).…”
Section: Nature Of Collagenmentioning
confidence: 93%
“…Probing drug-cell interactions with spectroscopic techniques has become increasingly popular and can contribute to the understanding of the mode of action of the drug at a cellular level 25, 26 . The majority of spectroscopic cellular studies reported to date are on cells that have been chemically fixed and are therefore often in a dehydrated state 17, 18, 23, 2729 . Fixation aims to preserve the structural and biochemical constituents of cells in as close to in vivo conditions as possible and is widely accepted in the field of spectroscopy 29 .…”
Section: Introductionmentioning
confidence: 99%